1998
DOI: 10.1084/jem.187.5.743
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sialic Acid Binding Site on Factor H Mediates Serum Resistance of Sialylated Neisseria gonorrhoeae

Abstract: SummaryFactor H (fH), a key alternative complement pathway regulator, is a cofactor for factor I-mediated cleavage of C3b. fH consists of 20 short consensus repeat (SCR) domains. Sialic acid binding domains have previously been localized to fH SCRs 6-10 and 13. To examine fH binding on a sialylated microbial surface, we grew Neisseria gonorrhoeae in the presence of 5 Ј -cytidinemonophospho-N -acetylneuraminic acid, which sialylates lipooligosaccharide and converts to serum resistance gonococci previously sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
345
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(357 citation statements)
references
References 81 publications
10
345
1
1
Order By: Relevance
“…The differences between variations (compared with S1959) were analyzed by ANOVA. LPS protecting bacteria from human serum has also been observed by others (Joiner et al 1986;Nawrot et al 1995;Ram et al 1998). One can postulate that the smooth LPS forms activate complement and deposit C3 on the long polysaccharide chains and in this way keep MAC formation at a distance from the bacterial cell membrane.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The differences between variations (compared with S1959) were analyzed by ANOVA. LPS protecting bacteria from human serum has also been observed by others (Joiner et al 1986;Nawrot et al 1995;Ram et al 1998). One can postulate that the smooth LPS forms activate complement and deposit C3 on the long polysaccharide chains and in this way keep MAC formation at a distance from the bacterial cell membrane.…”
Section: Discussionsupporting
confidence: 54%
“…Complement system activation is an important factor in the human defense system against bacterial pathogens (Burns and Hull 1998;Fischer et al 1997;Joiner et al 1986;Nawrot et al 1995;Ram et al 1998). The presence of O-polysaccharide on the surface of the P. mirabilis S1959 strain protected that strain from complementmediated lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although strain-specific properties have been associated with resistance to complement-mediated killing (i.e. serum resistance) in vitro, most clinically isolated gonococci initially exhibit serum resistance (Densen, 1989;de la Paz et al, 1995;Ram et al, 1998;Vogel and Frosch, 1999). Ram et al (1998) suggested that an increased conversion of C3b to iC3b on the gonococcal surface might contribute to serum resistance in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that C H alternative pathway inactivation occurs with N. gonorrhoeae infection (Densen et al, 1982;Densen, 1989;Wetzler et al, 1992;de la Paz et al, 1995;Ram et al, 1998;Jarvis et al, 1999;McQuillen et al, 1999;Vogel and Frosch, 1999). This prompted us to examine the role of CR3 in N. gonorrhoeae infection of the cervical epithelium.…”
Section: Analysis Of Cr3 Expression In Primary Human Cervical Epithelmentioning
confidence: 99%
“…For whole cell ELISA, the assay was performed as previously described with slight modifications [55]. Briefly, 10 8 CFU of bacteria were incubated with 20 μL of normal porcine serum (60 min at 37°C) as described above for western blotting.…”
Section: Methodsmentioning
confidence: 99%